PHYTOPLANKTON COMMUNITIES OFA FLOODPLAIN LAKE OF THE BRAHMAPUTRA RIVER BASIN, UPPER ASSAM B. K. - Sharma, B. K. (Journal of Indian Fisheries Association, 2015)
Phytoplankton (52 species; Bacillariophyceae > Chlorophyceae > Cyanophyceae > Euglenophyceae = Dinophyceae) of Samuajan heel, a tropical floodplain lake, registered identical mean annual richness (30 ± 4 species) in littoral and limnetic regions and depicted 33.3 - 77.2 % and 31.4 - 81.1 % community similarities respectively. Their abundance ranged between 137 ± 54 nil in littoral (Bacillariophyceae > Chlorophyceae) and 122 ± 45 nil (Chlorophyceae > Bacillariophyceae) in limnetic communities, comprised about 46% of net plankton and indicated winter peaks. This study depicted moderate species diversity, high evenness and low dominance of phytoplankton; species diversity showed significant direct correlation with richness and evenness and an inverse relationship with dominance. Phytoplankton showed significant positive relationship with transparency and silicate and negative with water temperature, rainfall, chloride and nitrate. Multiple regression revealed that ten abiotic factors accounted for > 80 - 98% of density variations of phytoplankton and the dominant groups. AN OVA depicted trends of significance in abundance of the biotic communities analysed. Keywords: Phytoplankton, floodplain lake, Brahmaputra basin, abundance, ecology